Avaliação do ensino fundamental de nove anos - Fabiana de Fatima Vieira (2015)
Elementary school of nine years was a educational policy adopted at national level to settle the large differences in the return (productivity) of children during elementary school. These differences wereobserved between those students who had already attended school, because they had access to early childhood education, and those who had not attended school until they are enrolled in elementaryschool. The idea was anticipating the life cycle of student decreasing in a year the age of compulsory registration in elementary school. Whereas this policy could have impacts on rate of enrollment and on probability of progression by series, this work analyzed these two indicatorsusing data from the PNAD (National Household Sample Survey) to check if these impacts were positive and substantial. The method used in this work was the method of double difference and the focus of the analysis was the state of Minas Gerais that was compared to two other units of thefederation: Sao Paulo and Bahia. The results showed that initially the anticipation of the life cycle of the student had no substantial impact on the registration and progression by series of elementary school students in Minas Gerais.